Shearing of guidewire coating by the tip of the electrocautery dilator during endoscopic ultrasound-guided gallbladder drainage - Koichiro Mandai; Takato Inoue (International Journal of Gastrointestinal Intervention)
We present the case of an 86-year-old man with acute gallstone-induced cholecystitis who underwent endoscopic ultrasound-guided gallbladder drainage. Despite the successful one-step gallbladder puncture and tract dilation using a fine-gauge electrocautery dilator, significant resistance was encountered during guidewire manipulation, ultimately revealing a peeled-off coating of the guidewire at the dilator tip. Although a subsequent attempt led to a successful stent placement, a peeled coating was observed in the duodenum. This case highlights the importance of careful attention to guidewire manipulation to prevent accidental shearing, not only through the needle but also through the electrocautery dilator. It emphasizes the necessity to practice caution in this technique-sensitive procedure to ensure both patient safety and procedural success.